Assessing the impacts of state-supported rail services on local population and employment: A California case study. (April 2018) - Talebian, Ahmadreza; Zou, Bo; Hansen, Mark
Abstract: The State of California has been financially supporting Amtrak intercity passenger rail services since 1976. This paper studies the impacts of this support on local population and employment at both county and city levels. We use datasets which include geographic, transportation, and socioeconomic characteristics of California counties and cities from 1950 to 2010. Propensity score, one-to-one matching models are employed to draw units from the control group, which are counties/cities that do not have a state-supported Amtrak station, to match with units from the treatment group, which are counties/cities that do. Using regression analysis, we find that state-support Amtrak stations have significant effect on local population in the long term, and the effect increases with time. However, the effect on civilian employment is almost non-existent. This suggests that state-supported Amtrak services can provide quality rail mobility and accessibility, which attract people to live in a rail-accessible region. However, the economic influence seems limited. Highlights: California has been financially supporting Amtrak intercity passenger rail services since 1976. We study the impacts of this support on local population and employment at both county and city levels. Propensity score matching models are used to draw units from the control group to match with units from the treatment group. State-support rail stations have significant effect on local population in the long term, and the effect increases with time. The effect on civilian employment is almost non-existent.